2015
DOI: 10.1016/j.freeradbiomed.2015.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine oxidase-A is an important source of oxidative stress and promotes cardiac dysfunction, apoptosis, and fibrosis in diabetic cardiomyopathy

Abstract: Oxidative stress is closely associated with the pathophysiology of diabetic cardiomyopathy (DCM). The mitochondrial flavoenzyme monoamine oxidase A (MAO-A) is an important source of oxidative stress in the myocardium. We sought to determine whether MAO-A plays a major role in modulating DCM. Diabetes was induced in Wistar rats by single intraperitoneal injection of streptozotocin (STZ). To investigate the role of MAO-A in the development of pathophysiological features of DCM, hyperglycemic and age-matched cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 43 publications
1
42
0
Order By: Relevance
“…Our data indicate that MAOs are responsible for the oxidative stress, ER stress and fibrosis underlying cardiac dysfunction in T1D. Another study identified MAO-A as an important source of ROS in STZ-treated rats, suggesting that its inhibition may improve cardiac contractility 15. These Authors focused on the later stages of DCM, characterized by reduced heart rate and contractility, and likely associated with reduced ejection fraction and dilation.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Our data indicate that MAOs are responsible for the oxidative stress, ER stress and fibrosis underlying cardiac dysfunction in T1D. Another study identified MAO-A as an important source of ROS in STZ-treated rats, suggesting that its inhibition may improve cardiac contractility 15. These Authors focused on the later stages of DCM, characterized by reduced heart rate and contractility, and likely associated with reduced ejection fraction and dilation.…”
Section: Discussionmentioning
confidence: 80%
“…More recently, monoamine oxidases (MAOs) have been shown to play a major role in the oxidative stress and development of several cardiovascular pathologies, including DCM 1215. These flavoenzymes, localized at the outer mitochondrial membrane, exist as two isoenzymes (MAO-A and -B) and present unique features among ROS sources.…”
Section: Introductionmentioning
confidence: 99%
“…The outer mitochondrial membrane serotonin-degrading enzyme MAO-A is another important source of H 2 O 2 in the heart. MAO-A shows greater activity in diabetic cardiomyocytes, and MAO-A inhibition results in improved contractile function in preclinical DM models, despite persistent hyperglycemia and hyperlipidemia (71). However, no difference in MAO expression or MAO-related oxidative stress was recently observed in right atrial appendages from cardiac surgery patients with or without DM (72).…”
Section: Obesity Diabetes and Oxidative Stressmentioning
confidence: 99%
“…DCM is different from hypertensive cardiomyopathy and is a unique cardiovascular disease due to hyperglycemia-induced oxidative stress (Privratsky et al 2003, Kamalakkannan & Prince 2006, Saandeep et al 2009, Murali et al 2013, Peake et al 2013, Umbarkar et al 2015, inflammation (Marfella et al 2003, Di et al 2005, Venkatachalam et al 2008, cardiac fibrosis (Fonarow & Srikanthan 2006), myocardial apoptosis (Fonarow & Srikanthan 2006) and mitochondrial damage (Boudina et al 2007, Ceriello 2008.…”
Section: Introductionmentioning
confidence: 99%